Pengaruh Sosial Media Marketing dan Kualitas Layanan terhadap Keputusan Pembelian Melalui Minat Beli Konsumen sebagai Variabel Intervening - Henny Welsa; Putri Dwi Cahyani; Fernicko Meidyansyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine the effect of Social Media Marketing (SMM), Service Quality (KL), Consumer Purchase Interest (MBK) on Purchase Decisions (KP) on Instagram 3second Social media. The population used in this study are consumers who have bought 3second products. The sample in this study was 126 respondents using the Non-Probability Sampling technique with a purposive sampling approach (taking samples with certain considerations, with the criteria of respondents who have ever accessed the 3second Instagram social media application. Data was taken using a questionnaire via google form, after the questionnaire results collected, the data was tabulated using MS Excel and analyzed using SPSS version 22. The results of this study indicate that Social Media Marketing (SMM) has no significant positive effect on Purchase Decisions (KP). Service Quality (KL) has a positive and significant effect on Purchase Decisions (KP). Consumer Buying Interest (MBK) has a positive and significant effect on Purchase Decisions (KP). The influence of Social Media Marketing (SMM) on Purchase Decisions (KP) through Consumer Buying Interest (MBK) as an accepted intervening variable. The Influence of Service Quality (KL) on Purchase Decisions (KP) through Consumer Purchase Interest (MBK) as an accepted intervening variable. Keywords: Social Media Marketing; Service Quality; Consumer Buying Interest; Buying decision